2013
DOI: 10.1530/eje-13-0145
|View full text |Cite
|
Sign up to set email alerts
|

Body iron stores and the risk of type 2 diabetes in middle-aged men

Abstract: Objective: We investigated the risk of type 2 diabetes mellitus (T2DM) over a wide range of body iron stores. Methods: Prospective cohort of 1613 men in the Kuopio Ischemic Heart Disease Risk Factor study, aged 42-60 years, free of T2DM and hereditary hemochromatosis at baseline in [1984][1985][1986][1987][1988][1989]. Baseline serum ferritin (sF) and serum-soluble transferrin receptor (sTfR) concentrations were used to predict incident T2DM. T2DM was assessed by questionnaires, blood glucose measurements, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
4
40
1
1
Order By: Relevance
“…Copper homeostasis and iron status are also related to GDM [61][63]. For example, high body iron stores, leading to unliganded iron, cause hydroxyl radical formation via Fenton chemistry and are significantly associated with a greater risk of T2DM [22], [64][67]. Here, 29 of the women were included in a vascular sub-study where there was a gradation of declining endothelial function of resistance blood vessels ex-vivo, poorest in the 12 of the 18 women with prior GDM studied here and less marked in those with UQ, compared with controls defined the same way [3].…”
Section: Discussionmentioning
confidence: 99%
“…Copper homeostasis and iron status are also related to GDM [61][63]. For example, high body iron stores, leading to unliganded iron, cause hydroxyl radical formation via Fenton chemistry and are significantly associated with a greater risk of T2DM [22], [64][67]. Here, 29 of the women were included in a vascular sub-study where there was a gradation of declining endothelial function of resistance blood vessels ex-vivo, poorest in the 12 of the 18 women with prior GDM studied here and less marked in those with UQ, compared with controls defined the same way [3].…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal studies have previously shown an association between incident diabetes and higher baseline ferritin levels [10, 1216, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the sTfR-F has not yet been investigated for associations with any glycemic or insulin outcomes, except for a small correlation study in 110 female T2DM patients from Kuwait (39). Importantly, the sTfR-F-index may not be confused with the sTfR-F-ratio, which lacks the log 10 -transformation of ferritin in the denominator and that has been investigated for association with T2DM in several studies, all reporting inverse associations (11,13,37,40,41). This ratio in our as in other studies (11,13) showed an extremely strong correlation (Pearson rZK0.97) with ferritin, questioning its additional value.…”
Section: Stfr and Stfr-f-indexmentioning
confidence: 99%